(untitled) (Zien Journal of Social Sciences and Humanities, 2021)
The composition will consist of at least two components among the materials. There are composite materials - for example, there are plywood. In all other composites, the components can be divided into a matrix or a connector, and electrical energy - to fill. Composites are usually distinguished by the type of reinforcing filler or the substance of the Matrix.